Difference between revisions of "009B Sample Midterm 2, Problem 3"
Jump to navigation
Jump to search
Line 12: | Line 12: | ||
|- | |- | ||
| | | | ||
− | ::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=x^2+x.</math> Then, <math style="vertical-align: - | + | ::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=x^2+x.</math> Then, <math style="vertical-align: -5px">du=(2x+1)~dx.</math> Thus, |
|- | |- | ||
| | | | ||
− | :: | + | ::<math>\begin{array}{rcl} |
+ | \displaystyle{\int (2x+1)\sqrt{x^2+x}~dx} & = & \displaystyle{\int \sqrt{u}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{2}{3}u^{3/2}+C}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{2}{3}(x^2+x)^{3/2}+C.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
'''Solution:''' | '''Solution:''' | ||
Line 25: | Line 31: | ||
|We multiply the product inside the integral to get | |We multiply the product inside the integral to get | ||
|- | |- | ||
− | | | + | | |
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\int_1^2\bigg(2t+\frac{3}{t^2}\bigg)\bigg(4t^2-\frac{5}{t}\bigg)~dt} & = & \displaystyle{\int_1^2 \bigg(8t^3-10+12-\frac{15}{t^3}\bigg)~dt}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\int_1^2 (8t^3+2-15t^{-3})~dt.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 33: | Line 44: | ||
|We integrate to get | |We integrate to get | ||
|- | |- | ||
− | | | + | | |
+ | ::<math style="vertical-align: -16px">\int_1^2\bigg(2t+\frac{3}{t^2}\bigg)\bigg(4t^2-\frac{5}{t}\bigg)~dt=\left. 2t^4+2t+\frac{15}{2}t^{-2}\right|_1^2.</math> | ||
|- | |- | ||
|We now evaluate to get | |We now evaluate to get | ||
|- | |- | ||
− | | | + | | |
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\int_1^2\bigg(2t+\frac{3}{t^2}\bigg)\bigg(4t^2-\frac{5}{t}\bigg)~dt} & = & \displaystyle{2(2)^4+2(2)+\frac{15}{2(2)^2}-\bigg(2+2+\frac{15}{2}\bigg)}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{36+\frac{15}{8}-4-\frac{15}{2}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{211}{8}.} | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 44: | Line 63: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=x^4+2x^2+4</math> | + | |We use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=x^4+2x^2+4.</math> Then, <math style="vertical-align: -5px">du=(4x^3+4x)dx</math> and <math style="vertical-align: -14px">\frac{du}{4}=(x^3+x)dx.</math> Also, we need to change the bounds of integration. |
+ | |- | ||
+ | |Plugging in our values into the equation <math style="vertical-align: -4px">u=x^4+2x^2+4,</math> we get <math style="vertical-align: -5px">u_1=0^4+2(0)^2+4=4</math> and <math style="vertical-align: -4px">u_2=2^4+2(2)^2+4=28.</math> | ||
|- | |- | ||
− | | | + | |Therefore, the integral becomes |
|- | |- | ||
− | | | + | | |
+ | ::<math style="vertical-align: -14px">\frac{1}{4}\int_4^{28}\sqrt{u}~du.</math> | ||
|- | |- | ||
| | | | ||
Line 58: | Line 80: | ||
|We now have: | |We now have: | ||
|- | |- | ||
− | | | + | | |
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\int_0^2 (x^3+x)\sqrt{x^4+2x^2+4}~dx} & = & \displaystyle{\frac{1}{4}\int_4^{28}\sqrt{u}~du}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\left.\frac{1}{6}u^{\frac{3}{2}}\right|_4^{28}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{1}{6}(28^{\frac{3}{2}}-4^{\frac{3}{2}})} \\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{1}{6}((\sqrt{28})^3-(\sqrt{4})^3)}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{1}{6}((2\sqrt{7})^3-2^3).}\\ | ||
+ | \end{array}</math> | ||
|- | |- | ||
|So, we have | |So, we have | ||
|- | |- | ||
− | | | + | | |
+ | ::<math style="vertical-align: -16px">\int_0^2 (x^3+x)\sqrt{x^4+2x^2+4}~dx=\frac{28\sqrt{7}-4}{3}.</math> | ||
|} | |} | ||
Revision as of 13:52, 18 April 2016
Evaluate:
- a)
- b)
Foundations: |
---|
How would you integrate |
|
|
Solution:
(a)
Step 1: |
---|
We multiply the product inside the integral to get |
|
Step 2: |
---|
We integrate to get |
|
We now evaluate to get |
|
(b)
Step 1: |
---|
We use -substitution. Let Then, and Also, we need to change the bounds of integration. |
Plugging in our values into the equation we get and |
Therefore, the integral becomes |
|
Step 2: |
---|
We now have: |
|
So, we have |
|
Final Answer: |
---|
(a) |
(b) |